REMOTE SENSING ANALYSIS OF VERTICAL SURFACE DISPLACEMENTS AS AN INDICATOR OF UNDERGROUND STRUCTURE DEFORMATIONS - HUDAK, Vasyl; KRIL, Tetiana; ZATSERKOVNYI, Vitaliy (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. The paper is devoted to the analysis of vertical displacements based on remote sensing data as an identifier of hazardous engineering-geological processes in areas with underground infrastructure. The study was carried out on the example of the section of the tunnel between Demiivska and Lybidska stations of the Kyiv subway. In December 2023, processes of uneven compaction and vibration creep of the soil massif around the tunnel lining were detected, and there was a risk of loss of stability of the tunnel structures and an emergency. Methods. This study employs the Differential Interferometric Synthetic Aperture Radar (D-InSAR) method which allows monitoring of soil surface deformations through phase change analysis among radar images. The correction procedures were applied to mitigate noise in processed images caused by temporal and geometric decorrelation, atmospheric disturbances, and other noise interferences. Correction and filtering method, specifically Canny and Sobel linear filters, were used to improve accuracy. Their application to processed satellite images enhances the contours of recorded vertical displacements and reduces geometric distortion noise, preserving the structural integrity of the images. According to our calculations, effective anomaly detection in images of urbanized areas requires a minimum threshold of 25% in image contrast and clarity. The filters’ application for highlighting significant intensity changes achieved a 28% increase in clarity, indicating high processing effectiveness for further analysis of displacement maps and other parameters related to vertical shifts. Results. Abnormal zones of vertical displacements were identified within the study area based on vertical displacement data. During the 2022–2023 observation period, these zones shifted toward the metro tunnel axis. Vertical displacements directly above the area of subsidence near the ’Rozetka’ store were detected during the fifth observation period, October–December 2023, coinciding with the tunnel closure for repairs. Overall, displacement values shifted from negative in 2022 to positive in 2023, suggesting that displacements may have served as an early indicator of underground structure deformation activation. The use of filters allowed for more precise identification of displacement dynamics and localization of deformation zones throughout the observation periods. In the final period, the anomalous zone aligned with the location of tunnel deformations and recorded surface subsidence. Сonclusions. Using the example of the distillation tunnel section, we demonstrate the possibility of using the analysis of vertical surface displacements performed by D-InSAR together with a combination of Kenny and Sobel filters to track vertical surface displacements, which is important for monitoring the condition of underground facilities and preventing possible accidents. This study lays the foundation for further development of methodological approaches to the analysis of potential deformations of underground structures based on surface dynamics (vertical displacements). Further improvement of the methodology will help to ensure the accuracy and reliability of data in the context of monitoring underground structures.